Meaning-centered dream work with hospice patients: A pilot study. Issue 5 (October 2015) - Wright, Scott T.; Grant, Pei C.; Depner, Rachel M.; Donnelly, James P.; Kerr, Christopher W.
Abstract: Objective: Hospice patients often struggle with loss of meaning, while many experience meaningful dreams. The purpose of this study was to conduct a preliminary exploration into the process and therapeutic outcomes of meaning-centered dream work with hospice patients. Method: A meaning-centered variation of the cognitive–experiential model of dream work (Hill, 1996; 2004) was tested with participants. This variation was influenced by the tenets of meaning-centered psychotherapy (Breitbart et al., 2012). A total of 12 dream-work sessions were conducted with 7 hospice patients (5 women), and session transcripts were analyzed using the consensual qualitative research (CQR) method (Hill, 2012). Participants also completed measures of gains from dream interpretation in terms of existential well-being and quality of life. Results: Participants' dreams generally featured familiar settings and living family and friends. Reported images from dreams were usually connected to feelings, relationships, and the concerns of waking life. Participants typically interpreted their dreams as meaning that they needed to change their way of thinking, address legacy concerns, or complete unfinished business. Generally, participants developed and implemented action plans based on these interpretations, despite their physical limitations. Participants described dream-work sessions as meaningful, comforting, and helpful. High scores on a measure of gains from dream interpretation were reported, consistent with qualitative findings. No adverse effects were reported or indicated by assessments. Significance of Results: Our results provided initial support for the feasibility and helpfulness of dream work in this population. Implications for counseling with the dying and directions for future research were also explored.